Perbedaan Length of Stay dan Severity Level Pasien dengan Gangguan Kardiovaskular di RSUD Cilacap dan Hospital Sultan Abdul Aziz Shah Malaysia sebagai Indikator Sistem Casemix - Shalsa Sekar Kinasih; Yektiningtyastuti Yektiningtyastuti; Dion Romodon; Harry Fauzi; Norizanne Binti Abd Rahim; Okti Anggraeni (Universitas Malahayati, 2026)
ABSTRACT Inpatient care for individuals with cardiovascular diseases necessitates effective management due to significant clinical complexity and considerable usage of hospital resources. In the casemix system, Length of stay (LOS) and severity level are often utilized indicator to assess inpatient service performance and the efficacy of case management. Variations in the adoption of casemix systems among nations may affect inpatient care management and patient demographics. This study was to examine variations in Length of stay (LOS) and severity levels among patients with cardiovascular illnesses at RSUD Cilacap and Hospital Sultan Abdul Aziz Shah (HSAAS), Malaysia, as indications of case management within the casemix system. This study employs a quantitative methodology, characterized by a comparative-descriptive design and a retrospective approach. The study sample comprises secondary casemix data for cardiovascular patients during the Third Quarter (July–September 2025), including 473 patients from Cilacap Regional Hospital and 165 patients from HSAAS. The data analysis encompassed descriptive statistics, normality assessment, and comparison analysis employing the Mann–Whitney test for Length of stay and the Chi-Square test for severity level. The findings revealed disparities in Length of stay (LOS) and severity leveldistribution between RSUD Cilacap and HSAAS (p-value = 0.001). These variances indicate variations in inpatient care management and case characteristics within different casemix system frameworks. The duration of hospitalization and severity level are pertinent factors for assessing inpatient care management in cardiovascular patients. The examination of these indicators elucidates the function of case management in reconciling clinical complexity with service efficiency. Keywords: Cardiovascular Disease, Casemix System, Case Management, Length of Stay, Severity Level. ABSTRAK Perawatan rawat inap bagi individu dengan penyakit kardiovaskular memerlukan manajemen yang efektif karena kompleksitas klinis yang signifikan dan penggunaan sumber daya rumah sakit yang cukup besar. Dalam sistem casemix, length of stay (LOS) dan tingkat keparahan sering digunakan sebagai indicator untuk menilai kinerja layanan rawat inap dan efektivitas case management. Perbedaan dalam penerapan sistem casemix di antara negara-negara dapat memengaruhi manajemen perawatan rawat inap dan demografi pasien. Penelitian ini bertujuan untuk menganalisis variasi length of stay (LOS) dan tingkat keparahan di antara pasien dengan penyakit kardiovaskular di RSUD Cilacap dan Rumah Sakit Sultan Abdul Aziz Shah (HSAAS), Malaysia, sebagai indikator case management dalam sistem casemix.Penelitian ini menggunakan metodologi kuantitatif, dengan desain komparatif-deskriptif dan pendekatan retrospektif. Sampel studi terdiri dari data casemix sekunder untuk pasien kardiovaskular pada triwulan ketiga (Juli–September 2025), meliputi 473 pasien dari RSUD Cilacap dan 165 pasien dari HSAAS. Analisis data mencakup statistik deskriptif, penilaian normalitas, dan analisis perbandingan menggunakan uji Mann–Whitney untuk length of stay dan uji Chi-Square untuk tingkat keparahan. Hasil penelitian menunjukkan perbedaan dalam durasi rawat inap (LOS) dan distribusi tingkat keparahan antara RSUD Cilacap dan HSAAS (nilai p = 0,001). Perbedaan ini menunjukkan variasi dalam manajemen perawatan rawat inap dan karakteristik kasus dalam kerangka sistem casemix yang berbeda. Length of stay dan tingkat keparahan merupakan faktor penting dalam menilai manajemen perawatan rawat inap pada pasien kardiovaskular. Analisis indikator-indikator ini menjelaskan peran case management dalam menyeimbangkan kompleksitas klinis dengan efisiensi layanan. Kata Kunci: Case Management, Length Of Stay, Penyakit Kardiovascular, Severity Level, Sistem Casemix.